Design, Synthesis and Characterization of Covalent KDM5 Inhibitors. Issue 2 (7th December 2018) - Vazquez‐Rodriguez, Saleta; Wright, Miranda; Rogers, Catherine M.; Cribbs, Adam P.; Velupillai, Srikannathasan; Philpott, Martin; Lee, Henry; Dunford, James E.; Huber, Kilian V. M.; Robers, Matthew B.; Vasta, James D.; Thezenas, Marie‐Laetitia; et al.
Abstract: Histone lysine demethylases (KDMs) are involved in the dynamic regulation of gene expression and they play a critical role in several biological processes. Achieving selectivity over the different KDMs has been a major challenge for KDM inhibitor development. Here we report potent and selective KDM5 covalent inhibitors designed to target cysteine residues only present in the KDM5 sub‐family. The covalent binding to the targeted proteins was confirmed by MS and time‐dependent inhibition. Additional competition assays show that compounds were non 2‐OG competitive. Target engagement and ChIP‐seq analysis showed that the compounds inhibited the KDM5 members in cells at nano‐ to micromolar levels and induce a global increase of the H3K4me3 mark at transcriptional start sites. Abstract : Histone lysine demethylases (KDMs) are involved in the dynamic regulation of gene expression and play a critical role in several biological processes. Achieving selectivity over the different KDMs has been a major challenge for KDM inhibitor development. Potent and selective KDM5 covalent inhibitors were designed to target cysteine residues only present in the KDM5 sub‐family.